2005
DOI: 10.1158/0008-5472.can-04-3472
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chemotherapy-Resistant Human Ovarian Cancer Xenografts in C.B-17/SCID Mice by Intraperitoneal Administration of Clostridium perfringens Enterotoxin

Abstract: Ovarian cancer remains the most lethal gynecologic malig-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
108
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 25 publications
7
108
0
Order By: Relevance
“…Other in vivo studies of external therapeutic application of recombinant CPE also reported strong necrosis in the tumor tissues. 33,[35][36][37] In conclusion, we report the successful tumor-targeted CPE gene therapy in vitro and in vivo. This approach efficiently eradicates tumor cells, and provides an attractive therapeutic option for the potential local treatment of refractory solid tumors (including unresectable tumor lesions, residual tumors or recurrences), originating from colon, mammary, pancreas or prostate cancer, which overexpress claudin-3 or -4.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Other in vivo studies of external therapeutic application of recombinant CPE also reported strong necrosis in the tumor tissues. 33,[35][36][37] In conclusion, we report the successful tumor-targeted CPE gene therapy in vitro and in vivo. This approach efficiently eradicates tumor cells, and provides an attractive therapeutic option for the potential local treatment of refractory solid tumors (including unresectable tumor lesions, residual tumors or recurrences), originating from colon, mammary, pancreas or prostate cancer, which overexpress claudin-3 or -4.…”
Section: Discussionmentioning
confidence: 68%
“…Application of recombinant CPE protein leads to the dose-dependent rapid eradication of claudin-4-or claudin-3-overexpressing pancreas, breast or colon cancer cells in vitro and in vivo. 17,18,[33][34][35][36][37] The intratumoral in vivo application of recombinant CPE did not induce toxinassociated side effects, supporting its great therapeutic potential. However, these approaches require repeated, almost continuous regional or loco-regional application of recombinant CPE at doses ranging from 0.5 to 1.0 mg CPE per application to achieve therapeutic effects.…”
Section: Introductionmentioning
confidence: 76%
“…There have been previous reports to indicate that claudin-4 is upregulated in primary breast (Kominsky et al, 2004;Tokes et al, 2005), ovarian (Rangel et al, 2003;Agarwal et al, 2005;Santin et al, 2005), prostate (Long et al, 2001;Sheehan et al, 2007) squamous cell carcinoma (Morita et al, 2004) and pancreatic cancers (Michl et al, 2001(Michl et al, , 2003Nichols et al, 2004;Sato et al, 2004) but is downregulated in gastric cancer (Lee et al, 2005). In this study, the increasing prominence of claudin-4 compared with other candidate genes evaluated at both RNA and protein levels was confirmed with highest levels in PCa metastatic cells.…”
Section: Discussionmentioning
confidence: 97%
“…18 A recent report using an ovarian cancer mouse model has shown that intra-abdominal administration caused significant inhibition of tumor growth and extended survival in xenografted C.B-17/SCID mice. 19 In addition, another claudin family member, claudin-7, has also been found elevated in ovarian cancer and may represent another target for detection and/or therapy. 7 Although the importance of CLDN3 in cancer biology is becoming clear, the mechanisms of regulation of CLDN3 in ovarian and other cancers are still unclear.…”
Section: Introductionmentioning
confidence: 99%